KAJIAN STRATEGI KEBIJAKAN INDUSTRI OLAHAN KARET RIBBED SMOKED SHEET (RSS) BERBAHAN BAKU LATEKS KEBUN DALAM UPAYA PENINGKATAN MUTU PRODUK - Garli Marsantia; Erdi Suroso; Tanto Pratondo Utomo (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
Natural rubber processing demand has increased every year because of the demand from  tire industries and other rubber based industries.  The problem of RSS industries with raw material of field latex was low quality of final products.  The purposes of this study were to identify factors that affected quality of RSS (Ribbed Smoked Sheet) product and to construct  strategies to improve the quality of  RSS (Ribbed smoked sheet) products.  Data were collected in two ways, there were primary data and secondary data.  Data were analyzed using SWOT method and continued using qualitative (descriptive) method.  Weighting results showed for internal factors had strength value  of 2,879, and weaknesses value of 2,705 then the difference value +0.174.  While the weighting for external factors had opportunities value  of 2,410, and threats value  was 1.306. then the difference value was +1,433 .  The conclusion  that could be drawn from this research is that The quality of RSS product can be improved by  strictly implementing the standard operating procedure ,  developing human resource abilities, collaborating research with other institutions , implementing  and  monitoring the use  of SNI 06-2047-2002 for latex raw materials. Keywords : Ribbed Smoked Sheet, SWOT